Human tRNA(Lys3)(UUU) is Pre-Structured by Natural Modifications for Cognate and Wobble Codon Binding through Keto-EnolTautomerism - Vendeix, Franck A. P. (2011)
Human tRNA(Lys3)(UUU) (htRNA(Lys3)(UUU)) decodes the lysine codons AAA and AAG during translation, and also plays a crucial role as the primer for HIV-1 reverse transcription. The post-transcriptional modifications 5-methoxycarbonylmethyl-2-thiouridine (mcm(5)s(2)U(34)), 2-methylthio-N(6)-threonylcarbamoyladenosine (ms(2)t(6)A(37))and pseudouridine (ψ(39)) in the tRNA'santicodon loop are critical for ribosomal binding and HIV-1 reverse transcription. To understand the importance of modified nucleoside contributions, the structure and function of this tRNA's anticodon stem and loop domain were determined with these modifications at positions 34, 37 and 39, respectively (hASL(Lys3)(UUU)-mcm(5)s(2)U(37);ms(2)t(6)A(37);ψ(39)). Ribosome binding assays in vitrorevealed that the hASL(Lys3)(UUU)-mcm(5)s(2)U(34);ms(2)t(6)A(37);ψ(39)bound AAA and AAG codons, whereas binding of the unmodified ASL(Lys3)(UUU) was barely detectable. The UV hyperchromicity, the circular dichroism and the structural analyses indicated that ψ(39) enhanced the thermodynamic stability of the ASL through base stacking while ms(2)t(6)A(37) restrained the anticodon to adopt an open loop conformation that is required for ribosomal binding. The NMR-restrained molecular dynamics derived solution structure revealed that the modifications provided an open, ordered loop for codon binding. The crystal structures of the hASL(Lys3)(UUU)-mcm(5)s(2)U(34);ms(2)t(6)A(37);ψ(39) bound to the 30S ribosomal subunit with each codon in the A site showed that the modified nucleotides mcm(5)s(2)U(34) and ms(2)t(6)A(37) participate in the stability of the anticodon/codon interaction. Importantly, the mcm(5)s(2)U(34)•G(3) wobble base pair is in the Watson-Crick geometry, requiring unusual hydrogen bonding to G in which mcm(5)s(2)U(34) must shift from the keto to enol form. The results unambiguously demonstrate that modifications pre-structurethe anticodonas a key prerequisite for efficient and accurate recognition of cognate and wobble codons.